Development of Leishmania parasites in Culicoides nubeculosus (Diptera: Ceratopogonidae) and implications for screening vector competence - Seblova, V; Sadlova, J; Carpenter, S; Volf, P (Journal of medical entomology, 2012)
Biting midges of the genus Forcipomyia (Diptera: Ceratopogonidae) have recently been implicated as vectors of kinetoplastid parasites in the Leishmania enrietti complex. This study assesses susceptibility of one of the few successfully colonized Ceratopogonidae, Culicoides nubeculosus Meigen, to infection with Leishmania parasites infecting humans. While Leishmania infantum initially developed in the midgut of C. nubeculosus until 2 d postfeeding, parasite populations on day 3 were considerably reduced. Despite this, a polymerase chain reaction-based assay continued to indicate presence of L. infantum for up to 7 d after the bloodmeal. These findings are discussed within the wider context of implicating arthropods as vectors of Leishmania and it is suggested that conventional polymerase chain reaction use in vector-competence studies should be accompanied by direct microscopical observations.
Keywords: Ceratopogonidae; Insect Vectors; Leishmaniasis; leishmanióza; Leishmania enriettii; Animals; Female; ženské pohlaví; hmyz - vektory; Host-Parasite Interactions; zvířata; interakce hostitele a parazita